Moving to New Generation Databases (MongoDB Redis) - Punia, Yogesh (My University, 2014)
Demand for speed, manageability, distributed, open-source, agile development with schema-less databases, easier horizontal scalability leads to fixing of broken parts in MySQL or Oracle by introducing next generation databases also termed as NoSQL. These are modern web-scale databases which are introduced to handle emerging applications such as social network analysis, bioinformatics network analysis and semantic Web analysis where a wide variety of data is to be processed which needs continuous witness with a quick increase. A critical challenge these days is to have an effective management and analysis of data at a large-scale. In this thesis I have tried to make an effort to use a combination of NoSQL databases to replace traditional database like Oracle applied to information management system, comparing the traditional database system with combination of MongoDB and Redis and presents the performance comparison of these two schema. As mostly all the old legacy systems have backend as MySQL, so there is need for shifting from SQL to another database through which queries can be performed as like SQL. A conversion effort have been made in this thesis. The change of need of databases have driven this work, to replace old existing system to with new databases so the database have been converted by fetching the information from its schema step by step and then finally successfully converting the databases that do not require real time transaction like banking system.
Master of Engineering-Thesis
Keywords: MongoDB; Redis; NoSQL; computer science